2011
DOI: 10.1116/1.3657525
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of extreme-ultraviolet mask patterns using coherent extreme-ultraviolet scatterometry microscope based on coherent diffraction imaging

Abstract: Articles you may be interested inPhase defect characterization on an extreme-ultraviolet blank mask using microcoherent extreme-ultraviolet scatterometry microscopeIn extreme-ultraviolet (EUV) lithography, defect-free mask production is a critical issue for highvolume manufacturing. For mask inspection and metrology, we have developed a coherent EUV scatterometry microscope (CSM). It is a simple lensless system. An aerial image of the mask pattern is reconstructed with iterative calculation based on coherent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…The hybrid input-output (HIO) algorithm as developed by Fienup 4 is the most widely used method for reconstructing phase information from the Fourier transform modulus since it enables to avoid local minima. In the case of mask inspection for EUVL, periodic patterns can be reconstructed and defects' width can be estimated 5 . However, accuracy is not high enough to estimate the actual depth of the defect.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid input-output (HIO) algorithm as developed by Fienup 4 is the most widely used method for reconstructing phase information from the Fourier transform modulus since it enables to avoid local minima. In the case of mask inspection for EUVL, periodic patterns can be reconstructed and defects' width can be estimated 5 . However, accuracy is not high enough to estimate the actual depth of the defect.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] The sample phase defect was exposed using coherent EUV light, and the diffracted light was recorded using a CCD camera. To reconstruct the pattern image, the phase information of the diffraction image is required, but this information is not recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The periodic structures of the line-and-space (L/S) and hole patterns and the aperiodic structures were reconstructed well. 17 In addition to the conventional intensity images, the phase images were also acquired by the coherent EUV scatterometry microscope (CSM). 20 The EUV-phase shift value of an absorber structure and the phase difference in the L/S pattern with shadowing effects were evaluated, because they could cause actinic critical-dimension changes.…”
Section: Introductionmentioning
confidence: 99%
“…Gerchberg-Saxton 13 and HIO methods have been adopted in several recent studies 1,3,5,[14][15][16][17][18][19][20] for mask inspection in EUVL. Harada et al 1,14,17 reported the development of coherent scatterometry microscope to characterize mask defect.…”
Section: Application Of Hybrid Input-output For Mask Inspectionmentioning
confidence: 99%
“…In the case of mask inspection for EUVL, periodic patterns can be reconstructed and defects' widths can be estimated. 5 However, it was reported that conventional phase retrieval methods, such as HIO algorithm, were not robust to noise. 6,7 In practical applications, the noise is, therefore, limiting the accuracy.…”
Section: Introductionmentioning
confidence: 99%